AIOLOS Variants Causing Immunodeficiency in Human and Mice - Yamashita, Motoi; Morio, Tomohiro (Frontiers in Immunology, 2022)
AIOLOS is encoded by IKZF3 and is a member of the IKAROS zinc finger transcription factor family. Heterozygous missense variants in the second zinc finger of AIOLOS have recently been reported to be found in the families of patients with inborn errors of immunity. The AIOLOSG159R variant was identified in patients with B-lymphopenia and familial Epstein–Barr virus-associated lymphoma. Early B-cell progenitors were significantly reduced in the bone marrow of patients with AIOLOSG159R. Another variant, AIOLOSN160S was identified in the patients presented with hypogammaglobulinemia, susceptibility to Pneumocystis jirovecii pneumonia, and chronic lymphocytic leukemia. Patients with AIOLOSN160S had mostly normal B cell counts but showed increased levels of CD21lo B cells, decreased CD23 expression, and abrogated CD40 response. Both variants were determined to be loss-of-function. Mouse models harboring the corresponding patient’s variants recapitulated the phenotypes of the patients. AIOLOS is therefore a novel disease-causing gene in human adaptive immune deficiency.